PENGARUH HERDING BEHAVIOR DAN OVERCONFIDENCE TERHADAP KEPUTUSAN INVESTASI - Prisiliya, Deva Ayu; Moeljadi, Moeljadi (Jurnal Management Risiko dan Keuangan, 2022)
The Covid-19 pandemic which began at the end of 2019 resulted in increased public awareness of investment. The increase in public awareness of investing in the capital market occurs because people are starting to realize the importance of investing to protect their money. This study aims to analyze the effect of herding behavior and overconfidence on the investment decisions of young East Java investors in the Capital Market. This type of research is explanatory research with a quantitative approach. Explanatory research is research that explains the relationship between variables through hypothesis testing. This study has 113 young investors sample in East Java obtained through the distribution of google form questionnaires using the purposive sampling technique. This research uses multiple regression analysis methods with the SPSS application. The results of this study indicate that herding behavior and overconfidence variables have a significant effect on the investment decisions of young investors in East Java. This research implies that investors must be more careful in making their investment decisions to avoid herding and overconfidence behavior that can harm their investment.